O PIBID de Ciências Sociais da Universidade Federal de Mato Grosso e a formação de professores de Sociologia para a Educação Básica - Francisco Xavier Freire Rodrigues (Universidade do Vale do Rio dos Sinos (UNISINOS), 2015)
This article analyzes the contributions of the Institutional Scholarship Program for Initiation (PIBID) of Social Sciences of the Federal University of Mato Grosso in the training of Sociology teachers for basic education in Cuiabá (Mato Grosso State). The main objective of this paper is to discuss the scope and the limitations that the conceptions and practices prevailing in the public schools of basic education and higher education institutions that train teachers, on the one hand, and the factors that influence recruitment for the teaching career, on the other, may bring to the purposes of the recent Institutional Scholarship Program for Initiation into Teaching (PIBID-CAPES). This is a qualitative investigation that has as its main techniques bibliographical review, ethnography at the PIBID schools and interviews with scholarship holders and supervisors. Since the Program is part of a wider set of actions that aim to establish a public policy for teacher training and basic education, the first part of the article describes the goals and principles that give support to the proposal. The second part is devoted to the assessment of the impact of training actions of the PIBID of Social Sciences at the Federal University of Mato Grosso on students (both scholarship holders and non-scholarship holders) and to the contextualization of the experience in the more general framework of this teacher training course. Finally, in the light of the experiences described in the second part, the article presents an assessment of current features of the educational systems that can prevent, if they not changed, the objectives pursued by the Program, viz. fostering the improvement of training and the enhancement of the teaching career, integrating the theoretical and practical training in the curriculum of the courses with the inclusion of schools as loci of training.